Compassion fatigue in helping professions: a scoping literature review - Mohd Noor, Amelia; Suryana, Dodi; Engku Kamarudin, Engku Mardiah; Mahadir Naidu, Noor Banu; Kamsani, Siti Rozaina; Govindasamy, Priyalatha (BioMed Central, 2025)
Background: Generalizing the concept of compassion fatigue across healthcare settings or professions is difficult because compassion fatigue is a complex and abstract concept. Compassion fatigue is described as a result in the form of behaviors and emotions resulting from learning of another person's traumatic event. Compassion fatigue is considered a 'cost of caring.' This study was a scoping literature review that aimed to identify what is known about compassion fatigue in helping professions. Methods: A systematic search was conducted on electronic databases, namely ScienceDirect, PubMed, and Taylor and Francis. Data analysis was conducted using PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). Study results were mapped based on the following criteria: 1) conceptual analysis; 2) predictor factors; and 3) research progress. A total of 43 articles met the inclusion and eligibility criteria for further review in this scoping literature review. Results: The results showed that it is difficult to imagine how a conceptual model of compassion fatigue could be equally relevant and applicable to various helping professions. Factors that can influence compassion fatigue are divided into personal factors (professional factors and sociodemographic factors), such as resilience, burnout, moral courage, emotional control, mindfulness, work experience, professional competence, and professional efficacy, and work-related factors such as traumatic experiences, life disorders, number of patients treated, job satisfaction, emotional support, social support, and fluctuations in interactions with suffering patients. Research on compassion fatigue has developed a lot, especially in the health sector, especially nursing using experimental, cross-sectional, and literature review research methods. Conclusion: Further analysis is needed in developing a conceptual analysis of compassion fatigue that focuses on other fields of work more specifically and comprehensively by paying attention to, aspects, determinants, and validity of compassion fatigue symptoms.